The fragility of marriage in matrilineal societies - Parkin, R (Anthropological Society of Oxford, 2020)
Matrilineal descent and the societies that have it have long been seen as being more in need of explanation than patrilineal descent, which tends to be treated as humanity's default when discussing descent. There is a long history of theories of matrilineal exceptionalism in anthropology, dating from the theory of an evolutionary priority for ‘mother right' in the nineteenth century to its contemporary revival through what has become known as the ‘grandmother' hypothesis, positing female coalitions as prior in evolutionary terms, with a grandmother looking after her daughter's children so the latter can go gathering. Along the way matriliny has been explained with reference to horticulture, increased women's rights and the so-called ‘matrilineal puzzle'. However, it is also reasonable to suggest that matrilineal systems are not simply mirror images of patrilineal ones and that they potentially have characteristics of their own such as the ‘visiting husband' phenomenon and the more frequent tendency generally for the marriage bond to be weak and unimportant. The article explores these latter aspects further.